The big country [videorecording (Blu-Ray)] - Wyler, William, 1902-1981; Wyler, William, 1902-1981; Peck, Gregory, 1916-2003; Peck, Gregory, 1916-2003; Simmons, Jean, 1929-2010; Heston, Charlton; Baker, Carroll, 1931-; Ives, Burl, 1909-1995; Bickford, Charles, 1891-1967; Connors, Chuck, 1921-1992; Bedoya, Alfonso, 1904-1957; Webb, James R.; et al. (Twentieth Century Fox Home Entertainment, 2011)
An ex-sea captain moves out west to marry his fiancee and live on her father's ranch, but clashes with a farmhand and discovers problems with the neighbors, and eventually falls for a school teacher instead. Adapted from Donald Hamilton's novel.